Whole Genome Sequencing of SARS-CoV-2 Strains in COVID-19 Patients From Djibouti Shows Novel Mutations and Clades Replacing Over Time - Osman, Ikram Omar; Levasseur, Anthony; Brechard, Ludivine; Abdillahi Hassan, Iman; Salah Abdillahi, Idil; Ali Waberi, Zeinab; Delerce, Jeremy; Bedotto, Marielle; Houhamdi, Linda; Fournier, Pierre-Edouard; Colson, Philippe; Aboubaker, Mohamed Houmed; et al. (Frontiers in Medicine, 2021)
Since the start of COVID-19 pandemic the Republic of Djibouti, in the horn of Africa, has experienced two epidemic waves of the virus between April and August 2020 and between February and May 2021. By May 2021, COVID-19 had affected 1.18% of the Djiboutian population and caused 152 deaths. Djibouti hosts several foreign military bases which makes it a potential hot-spot for the introduction of different SARS-CoV-2 strains. We genotyped fifty three viruses that have spread during the two epidemic waves. Next, using spike sequencing of twenty-eight strains and whole genome sequencing of thirteen strains, we found that Nexstrain clades 20A and 20B with a typically European D614G substitution in the spike and a frequent P2633L substitution in nsp16 were the dominant viruses during the first epidemic wave, while the clade 20H South African variants spread during the second wave characterized by an increase in the number of severe forms of COVID-19.